Strategi Pemasaran Pada RM Ayam Bakar Ma’lela Dalam Meningkatkan Minat Beli Konsumen (Generasi Milenial) Menggunakan Analisis Marketing Mix dan SOAR - Julyandaru, Cahya Putri; Ramadhan, Ady Tia (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the effectiveness of marketing mix marketing strategy analysis used by RM Ayam Bakar Ma’lela in increasing consumer buying interest (Millenial Generation) and poviding strategy proposals through SOAR Analysis. By understanding the characteristics of the millenial generation market and adjusting the marketing mix marketing strategy and their needs, it will increase their buying interest in Ayam Bakar Ma’lela products. The research modelis descriptive qualitative and focuses on the marketing strategy of RM Ayam Bakar Ma’lela. This variables in this research are the independent and depend on primary adn secondary data sources/ data collection methods include interview, observation and dokumentation. Based on the research conducted. It shows that RM Ayam Bakar Ma’lela is experiencing problems in the marketing mix marketing strategy, especially it terms of increasing consumer buying interest (Millenial Generation). The main factory influencing the instability of consumer purchase interest (Millenial Generation) is due to several marekting mix factors that have not been update. In an effort to overcome and minimize these risks, this research proposes the application of the SOAR analysis method to optimize marketing strategies and improve overall performance. Keyword: marketing strategy, marketing mix, SOAR analysis